La speranza progettuale. Ambiente e società by Tomás Maldonado. A Rereading (diségno, 2022)
Written by Maldonado in 1969, La speranza progettuale  was begun with the intention of formulating a systematic book on the [...] state of methodological research in the field of environmental design and planning. An endeavor, however, that appeared almost immediately unfeasible to its author due to the crisis of the very idea of design that pervaded the society of those years. Indeed, the years of youth protests are those in which Maldonado’s work should be contextualized, hence the change of perspective proposed in his reflections with which he sought to distance himself from a prevailing nihilistic vision of the future. [read more]